Pengobatan Gigi Gratis Santriwati Panti Asuhan Liga Dakwah Padang - Kornialia Kornialia; Hanim Khalida Zia; Yenita Alamsyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The 2018 basic health research of the Indonesian Ministry of Health reported that dental and oral health problems in adolescents have a large percentage. In contrast, caries or cavities have the most significant proportion at 45.3%, and swollen gums have 14%. Meanwhile, according to WHO, those who experience cavities in the 12-year-old age group are 43.43%, and in the 15-year-old age group are 33.54%. Of this proportion, only a few receive services from dental medical personnel. Community service was carried out at the Liga Dakwah Padang Orphanage. In the initial survey, when the team interviewed the foster teachers, it was discovered that so far, many female students have experienced dental and oral problems, ranging from toothache, cavities, bleeding gums, and canker sores. The foster teachers gave them available painkillers at the orphanage or went to the nearest health center to treat the students' toothaches. The community service aimed to improve the dental and oral health of the female students who live there by providing counseling, services, and dental and oral care to female students with dental and oral problems. The method of implementing the activity is: 1. Dental and oral health counseling, demonstration of brushing teeth, discussion and provision of pretest and posttest questionnaires, 2. Service activities were carried out at the dentist's practice for female students with dental and oral problems, such as caries, fillings, extractions, and tartar cleaning. The results of this service were that dental and oral health counseling activities were carried out for female students so that the level of knowledge of female students improved, increasing from 23.7% to 50.8%. Dental and oral care has been carried out for 49 female students with the following actions: cleaning of tartar to 11 people, fillings to 19 people, extractions to 14 people, and provision of toothache medicine to 5 people. This activity provided students access to dental services and improved their dental and oral health. This service activity concluded that there is an increase in female students' knowledge about dental and oral health and their level of dental and oral health.